Too little to live, too much to die: governing asylum seekers on the brink of death in Moria, Lesvos - T. Breuckmann (Geographica Helvetica, 2025)
For some time now, discussions in border studies have revolved around the biopolitical functions of refugee camps. From one perspective, the camps can be perceived to be humanitarian institutions. From another perspective, they can be considered institutions of necropolitics that allow asylum seekers to die, although they do not actively kill them. However, my own ethnographic research on Lesvos from 2018 to 2020 has shown that the biopolitics regulating refugee migration is not always situated at one of these extremes: for a long time, many asylum seekers have been maintained on the brink of death. Herein, I use governmentality theory and relational geography to examine how stabilization at this extremely fragile threshold has been maintained. I identify various strategic socio-spatial technologies that have been implemented on Lesvos and elucidate how heterogeneous power techniques were combined and practically related to each other in order to stabilize these modes of governing. This article also demonstrates how analysing modes of governing in relation to local spatial practices expands existing concepts by drawing a more complex and nuanced picture of power relations.